ANALISIS PROSES DAN HASIL PEMBELAJARAN TEKS DESKRIPSI DI KELAS 4 DI UPT SPF SDN 105345 SIDODADI RAMUNIA - Aisyah Khairina; Maysaroh; Siti Nurhayati; Abdurrahman Adisaputera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the learning process and outcomes of descriptive text instruction among fourth-grade students at UPT SPF SDN 105345 Sidodadi Ramunia. The research employed a qualitative descriptive method involving observation, interviews, and documentation. The findings revealed that the descriptive text learning process was conducted interactively through appropriate teaching methods that enhanced students’ writing abilities. However, some challenges were identified, including limited use of varied learning media and differences in student motivation. Overall, descriptive text learning in Grade 4 produced satisfactory outcomes, marked by significant improvement in students’ descriptive writing skills.